Tales of the city : drawing in the Netherlands from Bosch to Bruegel - Peters, Emily J. (Cleveland Museum of Art, 2022)
Featuring works by Hieronymus Bosch (c. 1450-1516), Jan Gossaert (c. 1478-1532), Maarten van Heemskerck (1498-1574), Pieter Bruegel the Elder (c. 1525-1569), Hendrick Goltzius (1558-1617), and others, this book positions drawing in the Low Countries in the sixteenth century as a dynamic, multifaceted practice. Drawings played roles as varied as the artists who made them: they were designs for prints, paintings, stained glass windows, decorative objects, and tapestries, as well as tools for presentation, translation, and the display of knowledge and virtuosity. The artists' diversified urban communities shaped their drawing practices, as did shifting cultural and political circumstances surrounding Protestant Reform and the Eighty Years' War. In addition to the book's four illuminating essays, many of the more than eighty catalogue entries-selected from the holdings of The Albertina Museum and the Cleveland Museum of Art-present new research. Exhibition: The Cleveland Museum of Art, USA (09.10.2022 - 08.01.2023)